Pengaruh Cold Water Immersion Terhadap Penurunan Denyut Nadi Recovery Pada Tim Sepak Bola Tombiano Fc - Taufiqur Rahman; Muhammad Agusman; Muh Kharil Fajri; Andi Saparia; Tri Murtono (Universitas Hamzanwadi, 2026)
Tombiano FC soccer players experienced physiological fatigue following high-intensity training, characterized by an increased heart rate and prolonged recovery time, while the recovery methods used were still passive in nature and lacked specific interventions. This study aimed to determine the effect of Cold Water Immersion (CWI) on reducing the recovery heart rate in Tombiano FC soccer players. The method used was a quantitative experimental design with a one-group pretest-posttest design. The sample consisted of 20 players selected using total sampling. The treatment involved immersing the lower body in water at a temperature of 10–15°C for 10–15 minutes. Recovery heart rate measurements were taken before and after the treatment using the palpation technique. Data analysis employed a paired-sample t-test following a normality test. The results showed that the average recovery heart rate without CWI treatment was 120.5 bpm, whereas after treatment it decreased to 104.9 bpm, representing an average decrease of 15.6 bpm. The statistical test yielded a significance value of p = 0.000 (p < 0.05), meaning H₀ was rejected and H₁ was accepted. In conclusion, CWI has a significant effect on reducing the recovery heart rate in Tombiano FC players; therefore, this method is effective and recommended as a cost-effective and easily applicable physiological recovery strategy.